(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
This article analyses the role of the radio in the fight against the mafia, highlighting the technical and communicative qualities of the medium and describing its possible uses in anti-mafia projects. The research has been conducted through the selection of different sources and the collection of interviews with exponents of the radio scene. It examines and compares historical cases, the most recent experiments and assesses future projects.